การสังเคราะห์ ไลซีน-กราฟต์ พอลิเมอร์ของพอลิฟีนอลจากชาเพื่อต้านโรคมะเร็ง - อิสราภรณ์ อิงสถิตธนวันต์ (จุฬาลงกรณ์มหาวิทยาลัย, 2017)
It has been known that epigallocatechin gallate (EGCG), a phenolic compound found in green tea, exhibits anticancer activity. Previous work has shown that the polymerized EGCG exhibits higher anticancer activity than EGCG. However most of the polymerized EGCG products are water immisible and possess sticky and gummy characteristic. Here we grafted lysine on to the insoluble polymerized EGCG (gum) via carbodiimide coupling, to improve its water dispersibility. We found that the obtained lysine-grafted products could self assembly into spherical-shaped particles with the size of 23±7.34 nm and the particles were water-dispersible. Moreover, cytotoxicity using MTT assay indicated that the lysine-grafted product inhibited the growth of HepG2 liver cancer cells more effectively than the ungrafted material.